Research on the Application of the “Insurance + Futures” Model for Agricultural Products in Addressing Price Fluctuations - Wang Yiran (SHS Web of Conferences)
The price fluctuation of agricultural products has brought challenges to the stability of agricultural producers and related industrial chains. Traditional agricultural futures and price risk management tools have been unable to fully meet the needs of modern agricultural development. In recent years, “insurance + futures” model, as an innovative risk management tool, has gradually shown its unique advantages in coping with the price fluctuations of agricultural products. This paper takes “insurance + futures” model as the research object, discusses its application mechanism and effect in agricultural product price risk management. Firstly, this paper analyses the causes of price fluctuation of agricultural products and its impact on agricultural producers, and expounds the operation mechanism of “insurance + futures” model. Then, through case analysis, the actual effect of this model in stabilizing farmers’ income and reducing the risk of price fluctuation is evaluated. Finally, some optimization suggestions are put forward for the existing problems of the model. The research shows that the “insurance + futures” model can effectively alleviate the negative impact of agricultural product price fluctuations, provide a new solution for agricultural risk management, and also provide theoretical support and practical reference for policy makers and market participants.